2009
DOI: 10.1037/a0014238
|View full text |Cite
|
Sign up to set email alerts
|

The differential impact of early father and mother involvement on later student achievement.

Abstract: The purpose of this exploratory study was to examine the direct and indirect effects of early parenting on later parental school involvement and student achievement. The sample, pulled from the first and second waves of the Panel Study of Income Dynamics – Child Development Supplement data set, consisted of 390 children ages 2–5 at time 1 and their families. Fathers’ and mothers’ participation in five dimensions of early parenting behaviors were assessed at time 1, while later parental school involvement and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 40 publications
5
33
0
3
Order By: Relevance
“…Our findings illustrate that father type and quality of father-adolescent relationship contribute unique associations with adolescents' school performance, boosting our understanding of the importance of fathers in their children's lives. These findings are particularly important, as prior findings in the literature on fathers' unique contribution to adolescents' outcomes, above and beyond mothers' contributions, have been inconsistent (Cherlin & Furstenberg, 1994;Martin et al, 2010;McBride et al, 2009;Vogt Yuan & Hamilton, 2006). Our findings indicate that not only are fathers important, but there are differences in outcomes depending upon the type of father relationship.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Our findings illustrate that father type and quality of father-adolescent relationship contribute unique associations with adolescents' school performance, boosting our understanding of the importance of fathers in their children's lives. These findings are particularly important, as prior findings in the literature on fathers' unique contribution to adolescents' outcomes, above and beyond mothers' contributions, have been inconsistent (Cherlin & Furstenberg, 1994;Martin et al, 2010;McBride et al, 2009;Vogt Yuan & Hamilton, 2006). Our findings indicate that not only are fathers important, but there are differences in outcomes depending upon the type of father relationship.…”
Section: Discussionmentioning
confidence: 54%
“…For example, some studies have reported that children with stepfamilies have lower academic achievement and more problem behaviors (Cherlin & Furstenberg, 1994), while other studies have illustrated that the level of involvement is important, so that highly involved stepfathers were associated with academic outcomes for their stepchildren similar to those of children with resident biological fathers (Emmott & Mace, 2014;Vogt Yuan & Hamilton, 2006). However, there is some evidence that greater fathers' involvement in later schooling is correlated with lower achievement, possibly because fathers become more highly involved when students are already struggling (McBride, Dyer, Liu, Brown, & Hong, 2009). Finally, little is known about the influence of having an adoptive father on child outcomes, which is an important consideration since adoptive fathers make a legal and deliberate choice to become a father (Baumann, 1999).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Valued mainly for their financial and instrumental support, men have frequently been given the role of second object or first stranger (Liebman & Abell, 2000), often being called the forgotten parent (Ross, 1979). The father figure has been represented in an imprecise and ambiguous way, distorted by several studies in which the relationship and the father's presence are evaluated by theories originally conceived to study the relationship between mother and child (Ford, Nalbone, Wetchler, & Sutton, 2008;McBride, Dyer, Liu, Brown, & Hong, 2009). Despite the fact that previous research has focused almost exclusively on the mother-child relationship, the role of the father as a caregiver and the specificities of his physical and emotional involvement with the child have been a source of special interest, both in the scientific community and society in general (Fägerskiöld, 2008;Lamb, 1986;Premberg, Hellström, & Berg, 2008).…”
mentioning
confidence: 99%